Creation of a paediatric head voxel model database for dosimetric applications. (September 2016) - Touyz, N.; Stratis, A.; Zhang, G.; Jacobs, R.; Bogaerts, R.; Bosmans, H.
Abstract : Introduction: CBCT is a recently introduced imaging modality in dentomaxillofacial radiology with increasing applications to paediatric cohorts. To accurately estimate the radiation induced risk via Monte Carlo (MC) simulations, age and gender specific head and neck voxel models should be built. These models will enable organ dose calculations and accurate risk estimation via effective dose (ED) or Life Attributable risk (LAR). Purpose: To design a head and neck voxel model database for MC dosimetry. Methods and materials: Our voxel models were based on organ segmentation of CT image datasets with following characteristics: represent a complete head; have a good low contrast resolution (as the many soft tissues are close in density), have the thyroid included in the scan. Using our PACS database, 13 datasets of paediatric patients from 5 to 14 years old were found to meet the requirements for further processing. From each CT scan, 22 organs were manually segmented on an organ by organ using ImageJ, Matlab tools and human atlases (example:http://headneckbrainspine.com/Neck-CT.php ). Organ masses were compared to ICRP reference values. Results: 13 paediatric voxel phantoms were created and compared favourably with ICRP values: 7 males and 6 females. The in-plane resolution of the phantoms, determined by the axial voxel size dimensions, ranges from 0.21 × 0.21 mm 2 to 0.48 × 0.48 mm 2 ; the z resolution ranges from 0.6 mm to 3.22 mm. Conclusion: The database for paediatric CBCT applications can now be used for detailed dose and risk applications.